2018
DOI: 10.3389/fneur.2018.00213
|View full text |Cite
|
Sign up to set email alerts
|

The Length of SNCA Rep1 Microsatellite May Influence Cognitive Evolution in Parkinson’s Disease

Abstract: BackgroundAlpha-synuclein is a constituent of Lewy bodies and mutations of its gene cause familial Parkinson’s disease (PD). A previous study showed that a variant of the alpha-synuclein gene (SNCA), namely the 263 bp allele of Rep1 was associated with faster motor progression in PD. On the contrary, a recent report failed to detect a detrimental effect of Rep1 263 on both motor and cognitive outcomes in PD. Aim of this study was to evaluate the influence of the Rep1 variants on disease progression in PD patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 32 publications
(44 reference statements)
0
18
0
Order By: Relevance
“…Although no association of SNCA rs356219 with cognition was found in a previous study in PD, the identification of a haplotype in intron 4 of SNCA and its direct association with PD dementia further strengthened the possibility that alpha‐synuclein–related mechanisms are strongly associated with cognitive deficits in sporadic PD . The relationship between variability in its gene promoter (Rep1) allele length with cognition, however, was suggested when a population‐based study by Corrado and colleagues reported that PD carriers of long Rep1 alleles (263 bp) showed significantly increased risk of both dementia (hazard ratio [HR] = 3.03) and visual hallucinations (HR = 2.69) compared to carriers of shorter alleles (263 noncarriers), but cognitive test scores were not available in this report, in contrast to our study. A second study by Markopoulou and colleagues reported that the longer Rep1 genotypes associated with increased PD risk paradoxically had better motor and cognitive outcomes, but this study had significant methodological limitations, including the use of a telephone interview to determine cognitive status in a retrospective manner, rather than use of standardized cognitive tests …”
Section: Discussionmentioning
confidence: 99%
“…Although no association of SNCA rs356219 with cognition was found in a previous study in PD, the identification of a haplotype in intron 4 of SNCA and its direct association with PD dementia further strengthened the possibility that alpha‐synuclein–related mechanisms are strongly associated with cognitive deficits in sporadic PD . The relationship between variability in its gene promoter (Rep1) allele length with cognition, however, was suggested when a population‐based study by Corrado and colleagues reported that PD carriers of long Rep1 alleles (263 bp) showed significantly increased risk of both dementia (hazard ratio [HR] = 3.03) and visual hallucinations (HR = 2.69) compared to carriers of shorter alleles (263 noncarriers), but cognitive test scores were not available in this report, in contrast to our study. A second study by Markopoulou and colleagues reported that the longer Rep1 genotypes associated with increased PD risk paradoxically had better motor and cognitive outcomes, but this study had significant methodological limitations, including the use of a telephone interview to determine cognitive status in a retrospective manner, rather than use of standardized cognitive tests …”
Section: Discussionmentioning
confidence: 99%
“…Widespread aggregation of the α -synuclein protein into inclusions called Lewy bodies, which can be detected in both the central and peripheral nervous systems, is the pathological hallmark of the disease [142, 143]. It is currently believed that a higher α -synuclein burden is associated to a more severe PD phenotype [144]. TAMs may play a role in PD pathogenesis, influencing microglial activation and phagocytosis and regulating alpha-synuclein deposition.…”
Section: The Role Of Tams In Neurodegenerative and Neuroinflammatomentioning
confidence: 99%
“…Additionally, 263bp carriers have shown a four-fold increased risk of faster motor decline [ 15 ]. The strong biological link is further supported by studies that demonstrated that longer Rep1 allele carriers were more cognitively impaired [ 16 ] and at greater risk for dementia [ 17 ] than carriers of the shorter allele. No study, however, has yet investigated the relationship between Rep1 length and non-motor symptoms in PD.…”
Section: Introductionmentioning
confidence: 90%